2018
DOI: 10.1080/17567505.2018.1531646
|View full text |Cite
|
Sign up to set email alerts
|

A Legacy of Energy Saving: The Discussion on Heritage Values in the First Programme on Energy Efficiency in Buildings in Sweden, c. 1974–1984

Abstract: The paper analyses the 'energy savings plan for existing buildings' (EBB) introduced in Sweden after the first oil crisis of 1973, and how effects of policies on the built heritage were perceived and communicated to a wider public. A conflict between conservation aims and energy efficiency was constructed for the first time in Sweden. The programme was a huge investment made by the government to reduce the import of oil. At first, little consideration was taken to the fact that heritage values might be at risk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Our own research shows, however, that in recent history, conservation interests has been pitted against the goals of increased energy efficiency (Legn er and Leijonhufvud, 2019). In Sweden, building conservation has had to step aside for policies ultimately designed to boost IJBPA 38,4 the level of employment in the building sector and to upgrade the housing stock (Tunefalk and Legn er, 2019a).…”
Section: Literature Reviewmentioning
confidence: 91%
“…Our own research shows, however, that in recent history, conservation interests has been pitted against the goals of increased energy efficiency (Legn er and Leijonhufvud, 2019). In Sweden, building conservation has had to step aside for policies ultimately designed to boost IJBPA 38,4 the level of employment in the building sector and to upgrade the housing stock (Tunefalk and Legn er, 2019a).…”
Section: Literature Reviewmentioning
confidence: 91%
“…Our own previous studies of Swedish energy efficiency policies have concluded that EBB and ROT had a significant impact on heritage values in the built environment, while at the same time resulting in empirically based knowledge of the built environment in Sweden that previously had been missing (Legneŕ and Leijonhufvud, 2019;Tunefalk and Legneŕ, 2019). These studies have also demonstrated how the rationale for large energy-saving programmes changed over time from a reduced import of oil, via less dependency on nuclear power, to financial stimulations of the building sector, and in later years a mitigation of climate change.…”
Section: Previous Researchmentioning
confidence: 99%
“…Starting in 1975, up to 35 per cent of the cost for energy retrofits could be subsidised, with an additional possibility of lending 65 per cent of the total cost of improvements. This made it possible for property owners to fund the whole investment using governmental grants and loans (Legneŕ and Leijonhufvud, 2019). These early subsides were part of the national programme EBB and included measures such as new windows, conversion to electric heating and additional insulation.…”
Section: Subsidies For Additional Façade Insulationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The loans mainly targeted building housing from the pre-war and war periods, as those buildings had the highest energy use. The energy loans were introduced without the consideration of potential negative visual impacts and influences on aesthetics and heritage values [32]. The applied exterior energy measures, such as additional insulation, new façade materials, and the replacement of windows, have been criticized for their lack of consistency with the buildings' original architecture that resulted in a disfigurement of older housing stocks [33].…”
Section: Case Study Selectionmentioning
confidence: 99%